Inference using non‐random samples? Stop right there!. Issue 5 (29th September 2021) - Hirschauer, Norbert; Grüner, Sven; Mußhoff, Oliver; Becker, Claudia; Jantsch, Antje
Abstract : Statistical inference allows researchers to learn things about a population using only a sample of data from that population. But if it isn't a random sample, inference becomes tricky or outright impossible, as Norbert Hirschauer, Sven Grüner, Oliver Mußhoff, Claudia Becker and Antje Jantsch explain Abstract : Statistical inference allows researchers to learn things about a population using only a sample of data from that population. But if it isn't a random sample, inference becomes tricky or outright impossible, as Norbert Hirschauer, Sven Grüner, Oliver Mußhoff, Claudia Becker and Antje Jantsch explain.